2021
DOI: 10.3390/app11156936
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Circadian Effectiveness in Lighting for Office Applications

Abstract: As one factor among others, circadian effectiveness depends on the spatial light distribution of the prevalent lighting conditions. In a typical office context focusing on computer work, the light that is experienced by the office workers is usually composed of a direct component emitted by the room luminaires and the computer monitors as well as by an indirect component reflected from the walls, surfaces, and ceiling. Due to this multi-directional light pattern, spatially resolved light measurements are requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 93 publications
(80 reference statements)
1
3
0
Order By: Relevance
“…Our measurements show a significant reduction of up to 60% for illuminance and MEDI when considering the FOV (at horizontal view and realistic settings, see Figure 3 and Figure 4 ). These results are consistent with the still sparse literature on this topic [ 5 , 46 ] and have a high relevance towards study design and replicability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our measurements show a significant reduction of up to 60% for illuminance and MEDI when considering the FOV (at horizontal view and realistic settings, see Figure 3 and Figure 4 ). These results are consistent with the still sparse literature on this topic [ 5 , 46 ] and have a high relevance towards study design and replicability.…”
Section: Discussionsupporting
confidence: 90%
“…The CIE recommends this approach in Annex A.6 of the standard CIE S 026:2018 [ 3 ]. Methods to achieve this include using an occlusion or radiance hood to limit the detection areas of photometers and spectroradiometers, or applying imaging measurements, e.g., from a luminance camera, followed by FOV-selective postprocessing [ 4 , 5 , 6 ]. However, these methods are not commonly used in current projects and studies, leading to potential inconsistencies and lack of standardization for non-image-forming effects of light (NIF).…”
Section: Introductionmentioning
confidence: 99%
“…Our measurements show a significant reduction of up to 60% for illuminance and MEDI when considering the FOV (at horizontal view and realistic settings, see Figures 3 and 4). These results are consistent with the still sparse literature on this topic [5,46] and have a high relevance towards study design and replicability.…”
Section: Further Discussion and Outlooksupporting
confidence: 89%
“…Many groups have worked on standardizing HCL evaluation criteria by considering the melanopic effects of ocular light in human-centric lighting [10][11][12][13]. Numerous attempts have been made to develop light-emitting diode (LED) spectral power distributions (SPDs) for human users in the HCL framework [14,15]. For LED office lighting, Islam et al [16] and Dangol et al [17] showed that color perception is related to the degree of acceptance by users, which can be assessed on scales of acceptable-unacceptable or like-dislike.…”
Section: Introductionmentioning
confidence: 99%